ANALISIS FAKTOR KETERLAMBATAN PADA PROYEK PEMBANGUNAN GEDUNG RUANG KELAS BARU MADRASAH 5 MALUKU TENGAH - Umarella, Risma; Leuhery, Lenora; Abdin, Maslan (Jurusan Teknik Sipil, 2024)
The construction project for the Central Maluku 5 Madrasah New Classroom Building project was carried out by CV Nadilla with a contract value of Rp. 2,891,000,000 and the duration of work is 119 calendar days in accordance with the contents of the work contract. The Central Maluku 5 Madrasah New Classroom Building Construction project experienced a delay in the 1st (first) week, with a cumulative plan of 0.15% but in reality it was 0.00%. then in the 14th week with a cumulative plan of 20.54% but in reality it was obtained 17.50%. and the 15th week with a cumulative plan of 44.26% but in reality it was obtained 42.03%. The research method uses data collection techniques and questionnaires with the types of data used are primary data and secondary data. Methods of data analysis using validity test, reliability test, factor analysis test, and F test and T test using toolsStatistical Program for Social Scine (SPSS) version 29 where in this method data will be obtained from the results of the questionnaire which will then be analyzed with the SPSS version 29 tool. The magnitude of the influence of the factors causing the delay in the Construction Project for the New Classroom Building for Madrasah 5 Central Maluku is due to the Labor factor (X1), Material (X2), Environmental (X3), and Managerial (X4), have an effect on the Delay variable (Y), because the significant value obtained is 0.000 which is smaller than 0.05 and the calculated F value obtained is 103.072 which is greater than the F table value of 2.74. The components of the factors causing the delay in the construction project of the New Classroom Building for Madrasah 5 Central Maluku were caused by the Labor factor (X1) with a valueStandardized Coefficients Beta of 0.369, Material (X2) with valueStandardized Coefficients Beta of 0.271, Environment (X3) with a valueStandardized Coefficients Beta of 0.222, and Managerial factor (X4) with valueStandardized Coefficients Beta of 0.196.